Neuropsychological functions in a pediatric case of partial agenesis of the corpus callosum: Clinical implications. Issue 2 (3rd April 2023) - Jacob, Jemima; Gupta, Rashmi
Abstract: The corpus callosum (CC) is involved in several cognitive processes and the interhemispheric transfer of information. The current case study investigated neurocognitive and emotional processes in a 7-year-old female with partial agenesis of the corpus callosum, with an absent splenium and posterior body, with comorbid autism and ADHD. We measured cognitive functions, such as response inhibition, error monitoring, attentional disengagement, and attention capture by irrelevant emotional stimuli. We found that response inhibition was intact in the case. When happy faces were used as stop-signals, it interfered with response inhibition compared to angry-face–stop-signals. Similarly, happy faces (relative to angry faces) interfered with error monitoring; irrelevant angry faces captured attention more than happy faces. Attentional disengagement functions were impaired in the case compared to healthy controls. The findings give an insight into the interaction between cognition and emotion in pediatric partial agenesis of the CC, and have important clinical and theoretical implications.